Where have all the Democrats gone? : the soul of the party in the age of extremes - Judis, John B.; Teixeira, Ruy A. (Henry Holt and Company, 2023)
"For decades, American politics has been plagued by a breakdown between the Democratic and Republican parties, in which victory has inevitably led to defeat, and vice versa. Both parties have lost sight of the political center of the American electorate, leading to polarization and paralysis. In Where Have All the Democrats Gone?, John B. Judis and Ruy Teixeira reveal the tectonic changes shaping the country's current political landscape that both pundits and political scientists have missed. The Democratic party, once the preserve of small towns as well as big cities and of the industrial working class and the newly immigrated, has abandoned and even actively alienated many of these voters. In this clarion and essential argument for common sense and common ground, Judis and Teixeira reveal the transformation of American politics and provide a much-needed wakeup call for Democrats and Republicans alike"--